Characteristic of Red Dragon Fruit Marmalade with Different Types of Sweeteners - Siti Susanti; Fajar Fikri Najar; Nurwantoro Nurwantoro (Journal of Applied Food Technology, 2021)
Red dragon fruit, a popular in Indonesia, has 30-35% portion of skin that has not been used and mostly become a waste. Previous study showed that the skin of red dragon fruit can be used for orange marmalade production. This study objectives are to analyze physical, chemical, and hedonic characteristic of red dragon fruit marmalade (RDFM) with different types of sweeteners. Physical characteristics were evaluated using L*a*b* colorimeter for color intensity, hand refractometer for total soluble solid, and cup and bob viscometer for viscosity. Whereas, chemical characteristics evaluation was carried out using aw meter for water activity, and hedonic characteristic testing by hedonic test. The results showed that the use of different types of sweeteners had a significant effect on the physical, chemical, and hedonic characteristics of RDFM. RDFM made with High-Fructose Syrup (HFS) had the highest brightness, RDFM with sorbitol had the highest redness and water activity (aw), RDFM with honey had the highest yellowness, RDFM with sucrose had the highest Total Soluble Solids (TSS), viscosity, overall hedonic test and the lowest water activity. It can be concluded that sucrose is the best sweetener to use for RDFM because of the highest overall hedonic test so that the final product will be easier to be accepted compared to the other sweeteners.